CONSUMER TRUST AND COGNITIVE DISSONANCE TOWARDS ONLINE REVIEWS IN SELECTED RESORTS: A PREFERENTIAL MODEL - Maria Corazon A. Buena; Eduardo G. Ong, Ph.D. (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
The increasing trends of using online consumer reviews as bases before the actual purchase of a product or service are now substantial in the consumer decision-making process. Consumers nowadays want not only the core products or services, but other offerings as well, and they usually verify these with the online reviews. The resort industry is not exempted from these deviations. This study particularly investigated the determinants of consumer trust in online reviews, the assertions of cognitive dissonance as part of pre-purchase behavior, and their effects on customers’ purchase likelihood. The study sites were selected resorts in Region IV in the Philippines, while the perspective of 500 customers located in the Philippines specifically in Metro Manila, Metro Davao and Metro Cebu were utilized. Initial findings showed that argument quality (.785), source credibility (.812) and perceived quantity of reviews (.785) had greatly influence consumer trust. However, the assertions of pre-purchase cognitive dissonance were not influenced by the determinants. Moreover, results revealed that pre-purchase cognitive dissonance (with a value of -0.084) has a negative impact on the purchase likelihood whereas consumers’ trust (with a value of 0.522) has a positive impact on the purchase likelihood.